ABDOMINAL MULTIVISCERAL TRANSPLANTATION, - Todo, Satoru (1995)
Under FK506-based immunosuppression, 13 abdominal multivisceral transplantations were performed in 6 children and 7 adults. Of the 13 recipients, 7 (53.8%) are alive and well with functioning grafts after 9 to 31 months. Six recipients died: three from PTLD, one from rejection, one from sepsis, and one from respiratory failure. In addition to rejection, postoperative complications occurring in more than isolated cases included PTLD (n=6), abdominal abscess formation (n=5), pancreatitis (n=3), and ampullary dysfunction (n=2). In addition, infection by enteric microorganisms was common during the early postoperative period. Currently, all 7 survivors are on an oral diet and have normal liver function. Two recipients (one insulin-dependent) require antidiabetes treatment, in one case following distal pancreatectomy and in the other after two episodes of pancreatic rejection. Thus, abdominal multivisceral transplantation is a difficult but feasible operation that demands complex and prolonged posttransplantation management. It is not yet ready for application and awaits a better strategy of immune modulation.